Epigallocatechin Gallate in Relapsing-Remitting Multiple Sclerosis: A Randomized, Placebo-Controlled Trial. Issue 3 (May 2021) - Bellmann-Strobl, Judith; Paul, Friedemann; Wuerfel, Jens; Dörr, Jan; Infante-Duarte, Carmen; Heidrich, Elmira; Körtgen, Benedict; Brandt, Alexander; Pfüller, Caspar; Radbruch, Helena; Rust, Rebekka; Siffrin, Volker; et al.
Abstract : Objective: To assess the safety and efficacy of epigallocatechin-3-gallate (EGCG) add-on to glatiramer acetate (GA) in patients with relapsing-remitting multiple sclerosis (RRMS). Methods: We enrolled patients with RRMS (aged 18–60 years, Expanded Disability Status Scale [EDSS] score 0–6.5), receiving stable GA treatment in a multicenter, prospective, double-blind, phase II, randomized controlled trial. Participants received up to 800 mg oral EGCG daily over a period of 18 months. The primary outcome was the proportion of patients without new hyperintense lesions on T2-weighted (T2w) brain MRI within 18 months. Secondary end points included additional MRI and clinical parameters. Immunologic effects of EGCG were investigated in exploratory experiments. Results: A total of 122 patients on GA were randomly assigned to EGCG treatment (n = 62) or placebo (n = 60). We could not demonstrate a difference between groups after 18 months for the primary outcome or other radiologic (T2w lesion volume, T1w hypointense lesion number or volume, number of cumulative contrast-enhancing lesions, percent brain volume change), or clinical (EDSS, MS functional composite, and annualized relapse rate) parameter. EGCG treatment did not affect immune response to GA. Pharmacologic analysis revealed wide ranging EGCG plasma levels. The treatment was well tolerated with a similar incidence of mostly mild adverse events similar in both groups. Conclusion: In RRMS, oral EGCG add-on to GA was not superior to placebo in influencing MRI and clinical disease activity over 18 months. The treatment was safe at a daily dosage up to 800 mg EGCG. It did not influence immune parameters, despite indication of EGCG being bioavailable in patients. Classification of Evidence: This study provides Class II evidence that for patients with RRMS, EGCG added to GA did not significantly affect the development of new hyperintense lesions on T2-weighted brain MRI. Trial Registration Information: Clinical trial registration number: NCT00525668.